Value of Personal Branding in COVID-19 Era - Reményik , Bulcsú; Szántó , Peter; Papp-Váry, Árpád Ferenc (Journal of Ecohumanism, 2024)
Purpose – This article aims to bring focus to the practical scenarios, individuals and businesses can use to build a strong Personal Brand. It raises directions on how PB can lead to business success, both financial and business goals-wise. Methodology/Approach – A sentiment analysis is used for understanding what strong Personal Branding is that serves as an quantitative indicator for this study. This article follows their traits in order to drive future research directions. Findings – An indisputable growth is shown of Personal Branding as an academic phenomenon. The COVID-19 pandemic amplified its importance in both digital and offline words. Furthermore, the principles of the circular economy provide a framework for sustainable personal branding, emphasizing resource efficiency and long-term adaptability. The article shows connections to employee branding, as well as methodological approaches and metrics that might be used for standardized measurement.